2023
DOI: 10.1038/s41423-023-01063-4
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding proteins TIA1 and TIAL1 promote Mcl1 mRNA translation to protect germinal center responses from apoptosis

Abstract: Germinal centers (GCs) are essential for the establishment of long-lasting antibody responses. GC B cells rely on post-transcriptional RNA mechanisms to translate activation-associated transcriptional programs into functional changes in the cell proteome. However, the critical proteins driving these key mechanisms are still unknown. Here, we show that the RNA binding proteins TIA1 and TIAL1 are required for the generation of long-lasting GC responses. TIA1- and TIAL1-deficient GC B cells fail to undergo antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…FUBP1-mediated up-regulation of MYC was reportedly due to increased transcription, but subsequent studies that either reduced or eliminated FUBP1 from cells have seen no effect on the level of MYC [ 37 , 38 ]. TIAR ( TIAL1 gene)–and possibly TIA1–regulation of MYC was through 3′UTR binding [ 35 ], but removal of TIA1 and TIAL1 genes in B cells did not alter MYC expression [ 39 ]. Comparatively, previous studies that have reduced HNRNPC expression have consistently shown reduced MYC expression [ 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…FUBP1-mediated up-regulation of MYC was reportedly due to increased transcription, but subsequent studies that either reduced or eliminated FUBP1 from cells have seen no effect on the level of MYC [ 37 , 38 ]. TIAR ( TIAL1 gene)–and possibly TIA1–regulation of MYC was through 3′UTR binding [ 35 ], but removal of TIA1 and TIAL1 genes in B cells did not alter MYC expression [ 39 ]. Comparatively, previous studies that have reduced HNRNPC expression have consistently shown reduced MYC expression [ 18 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly. the study of B cells defective in splicing factors hnRNPF, HuR, PTBP1, TIA1 (Monzón-Casanova et al, 2018 ; Osma-Garcia et al, 2021 , 2023 ; Huang et al, 2023 ), and now hnRNPL, suggest that either MYC expression or its transcriptional program are especially sensitive to splicing defects in activated B cells. The activity of E2F transcription factors is also necessary for S-phase entry (Lam et al, 1998 ; Hsia et al, 2002 ; Nie et al, 2012 ; Hinman et al, 2009 ; Yusuf et al, 2004 ; Pae et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA-binding proteins can modulate gene expression by affecting transcription, as well as by regulating the splicing and/or stability of the (pre)-mRNA transcripts, and thus have consequential cellular roles, including in B and other immune cells (Díaz-Muñoz and Turner, 2018 ; Turner and Díaz-Muñoz, 2018 ; Marasco and Kornblihtt, 2023 ). Splicing factors are emerging as important regulators of B cell biology, especially in activated B cells, with the consequent impact on the germinal center reaction (Qureshi et al, 2023 ; Monzón-Casanova et al, 2018 ; Diaz-Muñoz et al, 2015 ; Huang et al, 2023 ; Osma-Garcia et al, 2021 , 2023 ). hnRNPL belongs to the heterogeneous nuclear ribonucleoprotein (hnRNP) family of RNA-binding proteins, composed of ~20 major, and some less abundant, members; many involved in splicing (Geuens et al, 2016 ; Han et al, 2010 ; Marasco and Kornblihtt, 2023 ).…”
Section: Introductionmentioning
confidence: 99%